Identifying the influence of factors on the quality of critical reflection: Framing, frequency, and feedback (Journal of Applied Learning and Teaching, 2019)
In this study, we sought to identify the factors contributing to the quality of student critical reflections. Prior analyses of institutional assessment and evaluation data, including student reflection scores and experience with critical reflection pedagogies, had shown us that student experience and faculty experience with particular pedagogies were not adequate predictors of students’ ability to articulate their learning through reflective practices. Moreover, we suspected that instructor familiarity with critical reflection would have a much stronger impact than student’s prior experiences. After conducting two focus groups with [authors’ affiliated university] faculty and bolstering our existing literature review, however, we found that instructor and student experience with critical reflection may not impact the quality of a student’s critical reflection as strongly as the way in which reflective prompts were framed. Following subsequent qualitative analyses, the themes of framing, frequency, and feedback emerged, which were then used as a framework to guide the direction of future quantitative analyses. We discuss the implications for the implementation of critical reflection pedagogy and the improvement of student learning outcomes.